Understanding the Use of Digital Teaching Aids (BBM) in Microteaching of Hikmah Pedagogy: A Conceptual Proposal - zakaria, nik zuriani; Zulkifili, Hafizhah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This study aims to understand the use of digital Teaching Aids (BBM) in micro-teaching based on the Wisdom Pedagogy approach in the context of Islamic Education. The analysis focused on the effectiveness of digital BBM, implementation strategies and key challenges faced in the context of values and moral pedagogy. The study findings show that digital BBM such as interactive applications, animated videos, digital whiteboards and virtual platforms can increase student engagement, higher-order thinking skills (HOTS), and support reflective dialogue which is the core of Wisdom Pedagogy. However, there are significant constraints such as teachers' lack of understanding of the concept of wisdom, difficulty accessing BBM that is in line with Islamic values, as well as the level of infrastructure and professional training of teachers which is still insufficient. The study also found that the integration of digital BBM requires a reflective and contextual approach to be in line with the philosophy of Islamic education which emphasizes the development of students' intellect and morals. The contribution of this study is to provide a comprehensive overview of the potential and challenges of using digital BBM in contemporary pedagogy, in addition to suggesting improvements to policies, teacher training and curriculum design that are more relevant to the needs of 21st century education. The results are expected to strengthen microteaching practices that are value-based, reflective and centered on critical thinking in an effort to produce students who are holistic from an intellectual, emotional and spiritual perspective